2020
DOI: 10.3390/su12219048
|View full text |Cite
|
Sign up to set email alerts
|

‘Looking to the Future and the University in an Inclusive and Sustainable Way’: A Career Intervention for High School Students

Abstract: Career guidance needs new perspectives, considering the challenges that characterize our future, and it cannot exist without solidarity, inclusion, and attention to environmental challenges. It should also positively influence stakeholders to invest in the values of the 2030 Agenda recently proposed by the United Nations, and its encouragement to think about some of the emergencies that new generations will have to face in the future. Based on these premises, we designed and validated a sustainable career guid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 64 publications
0
9
1
Order By: Relevance
“…The data collected for this study showed that Informational Support (Factor 3) had the most significant influence in enhancing the development of career self-efficacy (r = .539, p < .01). The literature has implied that students' lack of confidence in developing a career path may be a psychological issue (see for example, Santilli et al, 2020), but the data in this study suggest that a lack of information may be the cause of the problem.…”
Section: Discussioncontrasting
confidence: 56%
“…The data collected for this study showed that Informational Support (Factor 3) had the most significant influence in enhancing the development of career self-efficacy (r = .539, p < .01). The literature has implied that students' lack of confidence in developing a career path may be a psychological issue (see for example, Santilli et al, 2020), but the data in this study suggest that a lack of information may be the cause of the problem.…”
Section: Discussioncontrasting
confidence: 56%
“…Regarding the relationship between career adaptability and personality, the research mainly includes self-esteem, EQ, active personality, personality characteristics, and the relationship between internal entrepreneurship and career adaptability [ 35 37 ]. In addition, some researchers have conducted follow-up research or intervention re-research on career adaptability [ 38 , 39 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the relationship between career adaptability and personality, the research mainly includes self-esteem, EQ, active personality, personality characteristics, and the relationship between internal entrepreneurship and career adaptability [33][34][35]. In addition, some researchers have conducted follow-up research or intervention re-research on career adaptability [36,37].…”
Section: Career Adaptabilitymentioning
confidence: 99%